Land for the People: The State and Agrarian Conflict in Indonesia - Anton Lucas, Carol Warren (Ohio University Press, 2013)
When Sundanese villagers carved â€œTanah Rakyatâ€ (Peopleâ€™s Land) onto the fairway of the Cimacan golf course in 1998, shortly after the official demise of the â€œNew Orderâ€ regime of President Suharto, they staked a claim against an unredeemed promise of the Indonesian revolution. Land and the welfare of ordinary people have been intrinsic to popular understandings of Indonesian nationhood since the early years of the nationalist movement.At every significant juncture in Indonesiaâ€™s recent history, land issues have played a pivotal role. â€œLand for the Peopleâ€ was the catchphrase of the land reform movement and peasant actions supported by the Communist Party (PKI) in the postrevolutionary period. Land issues were at the heart of the intense political conflict that ended in the anticommunist massacres of 1965â€“66 and the takeover by army general Suharto. Three decades later, land conflicts contributed to the overwhelming popular animosity that eventually ended Suhartoâ€™s authoritarian rule. Land tenure and access issues embody powerful tensions between elites and popular forces, between regional interests and central government, and between Indonesian national and transnational capital. The foundational importance of the land question was expressed in the 1960 Basic Agrarian Law, arguably the most important piece of legislation after the Indonesian constitution. Paradoxically this same piece of legislation oversaw diametrically opposed policies of the Old Order Sukarno (1950â€“65) and New Order Suharto (1966â€“98) regimes, and remains today a contentious focal point in the struggle for social justice by marginalized sectors of Indonesiaâ€™s population.